2013
DOI: 10.1016/j.ramb.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis in adults: clinical and epidemiological considerations

Abstract: Adult AD represents a clinical challenge that needs to be better characterized, since it can be misdiagnosed and interferes with the patient's social and personal life. The association of skin and respiratory atopic disease is frequent, and laboratory parameters such as circulating IgE levels and eosinophil blood count may be helpful to assess disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(39 reference statements)
2
11
0
2
Order By: Relevance
“…This finding is consistent with previous reports that AD is one of the most common skin diseases, with a prevalence of 1% to 3% in adults [22,23]. In previous population-based studies, the prevalence of AD was 1.2% in Korean males aged around 20 years, whereas the prevalence of AD among adolescents aged 12–18 years was 22.4% [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous reports that AD is one of the most common skin diseases, with a prevalence of 1% to 3% in adults [22,23]. In previous population-based studies, the prevalence of AD was 1.2% in Korean males aged around 20 years, whereas the prevalence of AD among adolescents aged 12–18 years was 22.4% [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…Most of the infants had mild to moderate severity; however, the EASI score increased with age, reaching >30% of that of severe adult patients. As in previous studies, the severity was either mild or moderate in >80% of the infants and children,1518 whereas a higher percentage (25%-31%) of patients in their adulthood had severe AD 734. Some other studies, however, showed contradictory data, with only 1.7% of adult patients having severe AD 19.…”
Section: Discussionmentioning
confidence: 60%
“…We also determined the effects of dupilumab on the serum levels of total IgE (normal range, ≤170 IU/ml) during the course of dupilumab treatment, based on the reported association of the total IgE level with the long-term response to treatment in AD patients. [19][20][21][22][23] Total IgE levels were measured in 7, 10, 13, 15, 9, and 5 of the 40 patients at 2, 4, 8, 16, 24, and 32 weeks after the start of dupilumab administration, respectively ( Fig. 3c and Table 5).…”
Section: Effects Of Dupilumab On Serum Levels Of Total Igementioning
confidence: 99%